2007
DOI: 10.1097/01.mcg.0000225658.30803.79
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Risk Factors of Reflux Esophagitis Among Adult Chinese Population in Taiwan

Abstract: The prevalence of reflux esophagitis in Taiwanese is 12% and most are mild grade and free from reflux symptoms. Hiatus hernia, male sex, and chronic obstructive pulmonary disease are 3 independent risk factors for development of reflux esophagitis. H. pylori infection did not protect subjects from reflux esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 28 publications
6
41
0
Order By: Relevance
“…18 In addition to the prevalence of reflux esophagitis, risk factors of erosive esophagitis among the Taiwanese and Koreans have been reported. 19 However, only the clinical parameters for reflux esophagitis have been studied in the Asian population. Whether the biochemical risk factors are relevant to erosive esophagitis in the general population remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition to the prevalence of reflux esophagitis, risk factors of erosive esophagitis among the Taiwanese and Koreans have been reported. 19 However, only the clinical parameters for reflux esophagitis have been studied in the Asian population. Whether the biochemical risk factors are relevant to erosive esophagitis in the general population remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Male sex, old age (>65 years old), hiatal hernia, smoking, alcohol, Caucasian race, and obesity are independent risk factors associated with asymptomatic esophagitis (8,(15)(16)(17). Atrophy, Helicobacter pylori infection, and peptic ulcer are not considered to be risk factors for provoking asymptomatic EE, while there are varying reports of association between BMI and asymptomatic EE (7,8,18).…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the prevalence of EE in symptomatic patients was 10.6%-13.8% (15,27) and was 7.1%-7.8% in subjects who had undergone a medical checkup (27,28). The prevalence of EE in Chinese and Taiwanese populations was 3.6%-12%, with 35%-50% not having typical reflux symptoms and 87% with mild reflux esophagitis of LA grade A or B (16)(17)(18)29). Differences in prevalence among these studies may be due to whether extraesophageal symptoms were included or not.…”
Section: Discussionmentioning
confidence: 99%
“…3e5 A previous study indicated that 5.0e14.5% of symptomatic people receiving upper gastrointestinal endoscopy were diagnosed with RE, 6 with most of these being mild in clinical grading. 7 Compared with younger patients, older patients with RE tend to have more severe disease on endoscopic grading and are more likely to have hiatal hernia. 8 As a result, the treatment response in older patients with RE may be different from that in younger patients.…”
Section: Introductionmentioning
confidence: 99%